Fatores que influenciam a descontinuidade de programas seis sigma: um estudo comparativo de casos - Mora Junior, Carlos Henrique (2009)
This research presents a study on the factors that influence the discontinuity of Six Sigma quality programs, and how these factors act in the organizational context. Despite the large number of publications showing the benefits and significant numbers of return obtained with the deployment of Six Sigma, and presenting the critical factors for success, are rare scholarly works that evaluated with rigorous research methods, what and how these factors influence the discontinuation of the program. This research is based on a multi-case study, exploratory and qualitative, in a sample of two Brazilian companies, one of manufacturing and marketing of electronic products sector, and other in the call center service sector. The strategy for data collection focused mainly on the method of semi-structured in-depth interviews, and analysis of the material of training of Six Sigma specialists. Were analyzed intra-case and inter-case from the event data from interviews and processed and organized with the help of qualitative analysis software called Atlas-ti. Through these analyses, it was possible to assess the similarities and differences between cases and establish the evidence necessary to answer the question of research. As a result of the research, it was concluded that eleven of the fifteen factors assessed interfere in different degrees in the discontinuity of the Six Sigma program. Among these, four had more relevance: 1 - lack of alignment of the Six Sigma program with the strategic objectives of the company, 2 - results and quality of projects and the program below the expectations of senior management, 3 - low involvement of the leaders of the company with the program and, 4 - inadequate point or stage of the life cycle of the company for adoption of Six Sigma. The identification of this last factor is one of the contributions of this work for this field of research, whereas this factor was still little explored in literature. It is also confirmed, according to literature, the results of Six Sigma projects are more influenced by factors related to management and leadership (soft factors) that technical, methodological or infrastructure factors (hard factors). Finally, this dissertation proposes a conceptual model that suggests an explanation of how these factors act and how these factors are inter-related to cause the complete disruption of the Six Sigma program in the organization